Effect of aerobic exercise along with core muscle strengthening in young individuals with constipation: randomized controlled trial - Gandhi, Riya Hemant; Gunjal, Sambhaji Balasaheb (International Journal of Research in Medical Sciences, 2023)
Background: Constipation is traditionally defined as infrequent bowel movements or hard faeces. Patients report a variety of symptoms, including decreased bowel motion frequency, straining, hard stools, the sensation of incomplete emptying, the sensation of anal blockage, or the use of digitation or positioning to aid defecation. Physical health, mental health, and social functioning are all compromised in affected individuals. Despite this, only one-fifth of constipated people seek medical attention. Constipation symptoms are reported by 10% to 20% of adults worldwide. This study investigated the effects of aerobic exercise along with core muscle strengthening on young individuals with constipation. Methods: The study included 50 participants having constipation. The participants were randomly allocated in two groups. The intervention period was of 4 weeks. The exercises were explained to all individuals and pre and post treatment PAC SYM (patient assessment of constipation symptoms) and PAC-QOL (patient assessment of constipation quality of life) questionnaire scoring along with Rome IV criteria was taken. Results: In group A, post-treatment values of PAC SYM and PAC QOL were significantly lower than pre-treatment values. The post-treatment comparison of two groups revealed a significant difference in PAC SYM and PAC QOL, with group B showing a significant reduction in PAC SYM and PAC QOL compared to group A. Conclusions: The present study concluded that individuals who underwent both aerobic and core strengthening training showed more improvement than individuals who performed aerobic training alone.